Adaptive fault tolerant control of dissimilar redundant actuation system of civil aircraft based on integral sliding mode control strategy. (September 2019) - Ijaz, Salman; Hamayun, Mirza Tariq; Yan, Lin; Ijaz, Hamdoon; Shi, Cun
In modern aircraft, the dissimilar redundant actuation system is used to resolve the actuator failure issues due to the common cause, thus increasing the system reliability. This paper proposes an adaptive integral sliding mode fault tolerant control strategy to deal with actuator fault/failure in the dissimilar redundant actuation system of civil aircraft. To cope with the unknown actuator faults, the adaptive integral sliding mode controller is designed where the modulation gain is made adaptive to the fault. To deal with the complete failure of certain actuator, the integral sliding mode control is integrated with control allocation scheme and distribute the control input signals to the redundant actuators. The performance of the proposed scheme is tested on the nonlinear model of dissimilar redundant actuation system, where the effect of external airload is accounted during simulations. The effectiveness of the proposed scheme is validated by comparing the simulations with the existing literature.